Perception Of Hering’s "DNA" Brand At The Point Of Sale (Stores) (ModaPalavra e-periódico, 2017)
This article aims to demonstrate the importance and the need for inserting the "brand DNA" into the architectural project of commercial spaces. Theoretical reference is rare in this area. Therefore, there is the importance of developing projects in commercial contexts that are more attuned to the "brand DNA", which is formed by elements that may be combined and recombined to express different identities. The goal of this study was to demonstrate, through the application of a questionnaire, which aspects of the atmosphere of the point of sale in two different stores were coherent with the "brand DNA" of the company Cia Hering - from the perspective of both the employees and consumers. Users generally identified the "brand DNA" both in the environment and in the product. However, some specific elements of the atmosphere of the point of sale presented reservations in addressing the brand DNA.
Keywords: DNA brand; commercial architecture; visual Merchandising